1987
DOI: 10.1007/bf00295878
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of subcutaneous glucose concentration: validation of the wick technique as a reference for implanted electrochemical sensors in normal and diabetic dogs

Abstract: Employing saline-impregnated cotton threads, an implanted-wick technique was adopted in dogs to obtain specimen from the subcutaneous interstitial compartment in order to estimate its glucose concentration. By measuring the protein, potassium and haemoglobin contents, the centrifuged wick fluid was shown to contain the interstitial concentration of solutes after an equilibration time of approximately 15 min. In normal and in diabetic animals the steady state subcutaneous glucose concentration was almost identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
69
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(77 citation statements)
references
References 23 publications
8
69
0
Order By: Relevance
“…Regittnig et al (5) found muscle and fat interstitial glucose values of 60 and 65% of blood glucose values during fasting conditions using the open-flow microperfusion technique. Interstitial values have been found to be identical to plasma values by some (8) and lower by 10 -55% by others (9,10), and microdialysis studies have shown glucose values that were lower by 15-30% (11)(12)(13). This is the first study with simultaneous continuous measurement of glucose in the interstitial fluid of adipose tissue, muscle tissue, and brain.…”
Section: Discussionmentioning
confidence: 62%
“…Regittnig et al (5) found muscle and fat interstitial glucose values of 60 and 65% of blood glucose values during fasting conditions using the open-flow microperfusion technique. Interstitial values have been found to be identical to plasma values by some (8) and lower by 10 -55% by others (9,10), and microdialysis studies have shown glucose values that were lower by 15-30% (11)(12)(13). This is the first study with simultaneous continuous measurement of glucose in the interstitial fluid of adipose tissue, muscle tissue, and brain.…”
Section: Discussionmentioning
confidence: 62%
“…Blood glucose concentrations are well correlated with subcutaneous glucose concentrations at steady-state (1)(2)(3)(4)(5). When the blood glucose concentration increases rapidly (3,4,(6)(7)(8)(9) or decreases (7,9,10) there is, however, a time lag, resulting in a transient difference between the blood and subcutaneous glucose concentrations.…”
mentioning
confidence: 99%
“…In the enzymatic glucose sensors, packaging technology, which was used to coat the sensors with biologically inert materials, is being widely used to prevent fouling and increase their biocompatibility. For example, cellulose acetate, 65 polyethylene glycol, 66 polyvinyl chloride, 67 polyurethane, 68 and Nafion 69 are being widely employed as biocompatible packaging materials.…”
Section: Non-enzymatic Microneedle Glucose Sensingmentioning
confidence: 99%